2017
DOI: 10.1038/s41598-017-16018-9
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 mimetics, optimal for Asian type 2 diabetes patients with and without overweight/obesity: meta-analysis of randomized controlled trials

Abstract: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are desirable for diabetes, especially in patients with overweight/obesity. We aimed to determine whether GLP-1RAs exhibit different glucose-lowering efficacies between Asian type 2 diabetes (T2D) patients with and without overweight/obesity. Randomized controlled trials were searched in EMBASE, MEDLINE, CENTRAL, and ClinicalTrials.gov. Studies published in English with treatment duration ≥12 weeks and information on HbA1c changes were included. The studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 41 publications
(147 reference statements)
3
13
0
Order By: Relevance
“…Our findings are in good agreement with a pooled analysis including 16 randomized controlled trials demonstrating similar efficacy of exenatide treatment between obese and non‐obese patients with T2D, except that the patients in that pooled analysis were divided into more BMI groups (≥20 to <25, ≥25 to <30, ≥30 to <35, and ≥35 kg/m 2 ) . A recent meta‐analysis focusing on Asian patients with T2D also found that patients with and without overweight/obesity can benefit from GLP‐1RAs . Another study conducted in obese Korean patients with T2D who were treated with 22‐week exenatide twice daily in combination with both metformin and sulfonylurea also found that baseline body weight and weight reduction during the intervention could not predict the HbA1c reduction in this population, although the median disease duration for patients in that study was 8 years and the median BMI was 30.78 kg/m 2 …”
Section: Discussionsupporting
confidence: 88%
“…Our findings are in good agreement with a pooled analysis including 16 randomized controlled trials demonstrating similar efficacy of exenatide treatment between obese and non‐obese patients with T2D, except that the patients in that pooled analysis were divided into more BMI groups (≥20 to <25, ≥25 to <30, ≥30 to <35, and ≥35 kg/m 2 ) . A recent meta‐analysis focusing on Asian patients with T2D also found that patients with and without overweight/obesity can benefit from GLP‐1RAs . Another study conducted in obese Korean patients with T2D who were treated with 22‐week exenatide twice daily in combination with both metformin and sulfonylurea also found that baseline body weight and weight reduction during the intervention could not predict the HbA1c reduction in this population, although the median disease duration for patients in that study was 8 years and the median BMI was 30.78 kg/m 2 …”
Section: Discussionsupporting
confidence: 88%
“…The selected RCTs were published between 2008 and 2021. Besides, in the included studies, 23 RCTs reported weight loss 7 8 9 10 11 12 13 16 17 18 19 20 21 22 23 24 25 26 27 28 37 , 20 RCTs provided BMI and WC as efficacy parameters 5 6 7 8 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 , 14 RCTs showed total cholesterol (TC), triglyceride (TG), and low density lipoprotein cholesterol (LDL-C) 7 8 9 10 12 13 16 17 21 23 24 26 27 28 , 15 RCTs displayed high density lipid-cholesterol (HDL-C) 8 9 10 11 12 13…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the weight loss effect of GLP-1A in the overweight/obesity patients with diabetes, recent studies demonstrated that GLP-1 also have an antiobesity effect in overweight/obese patients without diabetes. In 2015, Zhang et al systematically analyzed the eight randomized controlled trials (RCTs) of GLP-1RAs including liraglutide and exenatide and found that the treatment of overweight/obese patients without diabetes with GLP-1RAs can achieve –2.85 kg weight loss, significantly larger than control group 5 . Besides, in 2019, semaglutide, a recently approved novel GLP-1RA, was developed to treat overweight/obese patients without diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have demonstrated important benefits in obese NAFLD patients with and without T2DM [121][122][123]. Moreover, the metabolic efficacy of these therapeutic agents seems to be similar in patients without overweight/obesity [124]. GLP-1 RAs have direct hepatic actions: They can prevent accumulation of ceramides/sphingomyelins species, inflammation, and fibrosis and also induce changes in gut microbiota [125].…”
Section: Pharmacologic Treatmentsmentioning
confidence: 99%